Protectionism and Economic Growth: Causal Evidence from the First Era of Globalization - Niklas Potrafke; Fabian Ruthardt; Kaspar Wüthrich (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate how protectionist policies influence economic growth. Our empirical strategy exploits an extraordinary tax scandal that gave rise to an unexpected change of government in Sweden. A free-trade majority in parliament was overturned by a protectionist majority in 1887. We employ the synthetic control method to select control countries against which economic growth in Sweden can be compared. We do not find evidence suggesting that protectionist policies influenced economic growth and examine channels why. Tariffs increased government revenue. However, the results do not suggest that the protectionist government stimulated the economy in the short-run by increasing government expenditure.
Keywords: C33; D72; F10; F13; N10; O11; 330; protectionism; economic growth; first era of globalization; synthetic control method; causal inference